Pengaruh Perbedaan Warna Umpan terhadap Hasil Tangkapan Ikan Kurisi (Nemipterus sp.) pada Pancing Ulur di Perairan Desa Tanjung Labu Kecamatan Lepar Pongok Kabupaten Bangka Selatan - Fera Aprilia; M Tajuddin Noor; Exist Saraswati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This research was carried out to understand the effect of different types of bait on the catch of Kurisi fish (Nemipterus sp.) using hand lines in the waters of Lepar Pongok District, South Bangka Regency. This area is part of the Republic of Indonesia State Fisheries Management Area (WPPNRI) 711, which includes the waters of the Karimata Strait, Natuna Sea and South China Sea, as stipulated in Minister of Maritime Affairs and Fisheries Regulation No. 18 of 2014. Kurisi fish, which have high economic value and are the target of local fishermen, are a type of demersal fish that live in shallow waters with coral reefs. Sustainable fisheries management is very necessary to support the fisheries sector which plays an important role in the welfare of coastal communities. This research used three types of artificial bait, namely red rapia rope, blue rapia rope, and yellow rope using the Experimental Fishing method and Randomized Group Design (RAK). Catch data is measured in number of tails and weight (kg), then analyzed to determine the most effective bait in increasing catches. With these results, it is hoped that the research can contribute to improving the welfare of fishermen and support sustainable management of fisheries resources in the research area.